Penguatan Usaha Jamur Tiram sebagai Sumber Ekonomi Produktif pada Kelompok Tani Hutan Borneo Citra Lestari - rahman, rahman; Hariatama H, Fendy; Putri, Windy Utami (Kahayan : Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity aims to strengthen oyster mushroom cultivation as a productive economic source for the Borneo Citra Lestari Forest Farmers Group (KTH) in Kereng Bangkirai Village, Sabangau District, Palangka Raya City. The oyster mushroom business has been run by the group. The methods used in this activity include preparation and identification of needs, socialisation, improvement of technical capacity in oyster mushroom cultivation, strengthening of business management and group institutions, as well as evaluation and formulation of follow up actions. The main targets of this activity are group members who are directly involved in oyster mushroom cultivation and group administrators as decision makers. The results of the activity showed an increase in the members' understanding and skills in oyster mushroom cultivation techniques, increased awareness of the economic potential of the oyster mushroom business, and strengthened business management through simple financial record keeping and a clearer division of institutional roles. This activity had a positive impact on the group's readiness to develop the oyster mushroom business in a sustainable manner as a source of income and local economic empowerment